Fine-tuned organic photoredox catalysts for fragmentation-alkynylation cascades of cyclic oxime ethers - Le Vaillant, Franck (Royal Society of Chemistry, 2018)

(untitled) (Chem Sci)
Fine-tuned organic photoredox catalysts are introduced for the metal-free alkynylation of alkylnitrile radicals generated via oxidative ring opening of cyclic alkylketone oxime ethers. The redox properties of the dyes were determined by both cyclic voltammetry and computation and covered an existing gap in the oxidation potential of photoredox organocatalysts.